Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.2196/jmir.2777
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Cognitive Behavioral Therapy for Patients With Chronic Somatic Conditions: A Meta-Analytic Review

Abstract: BackgroundPatients with chronic somatic conditions face unique challenges accessing mental health care outside of their homes due to symptoms and physical limitations. Internet-based cognitive behavioral therapy (ICBT) has shown to be effective for various psychological conditions. The increasing number of recent trials need to be systematically evaluated and quantitatively analyzed to determine whether ICBT is also effective for chronic somatic conditions and to gain insight into the types of problems that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
142
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(165 citation statements)
references
References 72 publications
15
142
3
3
Order By: Relevance
“…The number of studies on ehealth interventions has grown rapidly in the last few years. Studies among patient or general populations have shown that e-health interventions enhance health and wellbeing, improve lifestyle and increase self-management for a broad range of diseases or risk factors (16)(17)(18)(19)(20)(21). In occupational health, however, articles on e-health interventions are relatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The number of studies on ehealth interventions has grown rapidly in the last few years. Studies among patient or general populations have shown that e-health interventions enhance health and wellbeing, improve lifestyle and increase self-management for a broad range of diseases or risk factors (16)(17)(18)(19)(20)(21). In occupational health, however, articles on e-health interventions are relatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings suggest iCBT as an effective treatment for comorbid symptoms of depression and anxiety in patients with somatic conditions [13] and effective psychological interventions for emotional distress related to coronary heart disease are characterized by CBT techniques [9]. Given this, the lack of effect of the iCBT intervention found in the present study may have several explanations.…”
Section: Discussionmentioning
confidence: 55%
“…To improve access to effective support, increased engagement in e-health solutions within the cardiac community has been called upon [10], with internet-based CBT (iCBT) representing an e-health solution that may improve access to acceptable, effective and cost-effective psychological treatment [11] iCBT has been found to reduce symptoms of depression and anxiety among adults with common mental health difficulties [12]. In addition, evidence suggests guided iCBT may improve disease-related functioning and reduce psychological distress in patients with chronic somatic conditions [13]. Furthermore, preliminary evidence suggests iCBT may reduce symptoms of depression and anxiety for adults with high cardiovascular risk [14].…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…eHealth has several important advantages, such as a greater reach of care and better access to care, less time consumption and travel costs for the patient and a great flexibility for therapist and patient. There are indications that eHealth interventions can be as effective as face to face treatments for various physical ailments [56]. Additionally, psychological interventions focused on mindfulness and acceptance, which are increasingly used in treating chronic conditions, offer promising possibilities for the psychological treatment of skin conditions [52].…”
Section: A U T H O R ' S C O P Y N O T F O R S a L E O R D I S T R I mentioning
confidence: 99%